83.7k views
2 votes
-3(2x + 1) = 2 (-3x -1)

2 Answers

2 votes

Answer:

Explanation:

calculator???? srry

User Yuttadhammo
by
4.9k points
3 votes

Answer:

No solution

0=1

The sides are not equal.

Explanation:


-3(2x + 1) = 2 (-3x -1)\\\\\mathrm{Expand\:}-3\left(2x+1\right):\quad -6x-3\\\\\mathrm{Expand\:}2\left(-3x-1\right):\quad -6x-2\\\\-6x-3=-6x-2\\\\\mathrm{Add\:}3\mathrm{\:to\:both\:sides}\\\\-6x-3+3=-6x-2+3\\\\Simplify\\\\-6x=-6x+1\\\\\mathrm{Add\:}6x\mathrm{\:to\:both\:sides}\\\\-6x+6x=-6x+1+6x\\\\Simplify\\\\0=1\\\\No \:solution\\\\\mathrm{The\:sides\:are\:not\:equal}

User Najeebullah Shah
by
5.6k points